1988
DOI: 10.1038/335070a0
|View full text |Cite
|
Sign up to set email alerts
|

Ciliary neurotrophic factor induces type-2 astrocyte differentiation in culture

Abstract: We have been studying a population of bipotential glial progenitor cells in the perinatal rat optic nerve and brain in an attempt to understand how cells choose between alternative fates in the developing mammalian central nervous system (CNS). This cell population gives rise initially to oligodendrocytes and then to type-2 astrocytes\ both of which apparently collaborate in sheathing axons in the CNS 2 .3. In vitro studies suggest that oligodendrocyte differentiation is the constitutive pathway of development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
138
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 323 publications
(144 citation statements)
references
References 28 publications
6
138
0
Order By: Relevance
“…Therefore, we reexamined the potential of PDGF-generated progeny to differentiate into astrocytes in the presence of CNTF, another factor known to induce astrocyte differentiation of O-2A progenitors (Hughes et al, 1988). We found that CNTF on its own did not induce GFAP expression in PDGF-generated progeny (Fig.…”
Section: Prps Are Distinct From Egf-responsive Nscsmentioning
confidence: 91%
“…Therefore, we reexamined the potential of PDGF-generated progeny to differentiate into astrocytes in the presence of CNTF, another factor known to induce astrocyte differentiation of O-2A progenitors (Hughes et al, 1988). We found that CNTF on its own did not induce GFAP expression in PDGF-generated progeny (Fig.…”
Section: Prps Are Distinct From Egf-responsive Nscsmentioning
confidence: 91%
“…Paravertebral sympathetic ganglia, dorsal root ganglia, and ciliary ganglia were dissected from chick embryos at the indicated embryonic day as described elsewhere (Lindsay et al, 1985;Hughes et al, 1988). Embryos were staged (Hamburger and Hamilton, 1951) to confirm developmental age.…”
Section: Embryonic Chick Neuron Culturementioning
confidence: 99%
“…LIF acts as a survival factor for sensory and motor neurons in the mature nervous system (reviewed in Turnley and Bartlett 11 and Murphy et al 12 ). In the developing central nervous system (CNS), LIF 13,14 inhibits self-renewal of neural precursor cells and promotes differentiation into astrocytes, similar to other LIF/gp130-related cytokines such as ciliary neurotrophic factor (CNTF) [13][14][15][16] and oncostatin M. 17 However, recent data suggest an opposite effect of the signal in neural precursor cells, specifically the maintenance of cortical precursor cells 18,19 in the undifferentiated state by increasing their self-renewal and inhibiting progression to astrocytic lineage. The mechanism by which gp130/LIFR signal performs such opposite roles remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%